TRANSPOR KREATININ MELALUI MEMBRAN KITOSAN DAN N-DODESIL KITOSAN - , EKA SULISTYANINGSIH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
A study on creatinine transport through membranes based on chitosan and N-dodecyl chitosan and its blend had been conducted. N-dodecyl chitosan was synthesized by alkylation with the reflux process. Membranes were prepared by inversion phase technique and MIP (molecularly imprinted polymer). Principle of phase inversion technique is change liquid phase to solid phase. Principle of MIP technique is templating molecules into membrane. Membranes morphology was characterized using SEM, water absorption was calculated and the stretch and tensile strength were measured using Universal Testing Machine. The creatinine transport was prepared with chitosan, N-dodecyl chitosan and its blend membrane using chamber, membrane separates the source and acceptor phase. Variables in this research were the concentration of creatinine as source phases, technique of membrane preparation and the composition of the chitosan membrane. The source phase were prepared 50 mL of creatinine 70, 100 and 130 ppm and acceptor phase 50 mL of distilled water, both of phase adjusted to pH 7.4. The concentration of creatinine after transport in the source phase and the acceptor phase was determined using picric acid under alkaline conditions using UV-Vis spectrophotometer at Î» 490 nm. The results of FTIR showed the success of the alkylation, be marked by the loss of bending vibration absorption of primary amines (-NH2) and appearance of aliphatic C-H stretching vibration absorption of dodecyl groups. The morphology of the MIP membranes appear more solid than PI. MIP chitosan membrane is the highest of tensile strength and % strain, 53.7 MPa and 17.35% respectively, while the lowest tensile strength is the MIP N-dodecyl chitosan with 14.1 MPa and the lowest strain was PI N-dodecyl chitosan membran of 5.35%. MIP chitosan membrane has the highest water absorption, 93.24%, while the lowest absorption was MIP N-dodecyl chitosan membrane at 61.71%. The results of creatinine transport show that concentrations of source phase using membrane MIP in the early transport was lower than PI membranes.